Edible agents with perceptible minds: A psychological study of human perception in human–food interaction - Takuma Shimoyama; Yuya Kume; Mei Yamagata; Hideyuki Takahashi; Yoshihiro Nakata (PLoS ONE, 2026)
Investigating the psychological and cognitive mechanisms of eating living beings is important for understanding ethical judgments and decision-making in eating behaviors. For example, the meat paradox describes a conflict about harming animals for food. In addition, perceiving a mind in a target has been shown to influence ethical judgment. However, experimentally investigating such food-related ethical themes is difficult, particularly when using actual animals, due to ethical constraints. Therefore, this study proposes an experimental framework using edible agents. Previous research developed a movable edible robot and examined the psychological and cognitive effects of eating moving food. Building on this, we developed an edible agent capable of social interaction through vocalization and evaluated its psychological effects. We examined how people perceive the minds of edible agents with different vocalization types and behaviors, and how this perception influences reluctance to eat and guilt. In the experiment, participants ( N = 1,094) viewed two videos in which edible agents exhibited different vocalizations and movements and evaluated their impressions. Factor analysis of 18 mind-perception items extracted two factors—Agency and Experience—with a cumulative contribution of 57.8% ( α = 0.941 and 0.862, respectively). Agency scores were significantly higher in Video 1 than in Video 2 ( W = 481,686, p < .001, r = 0.800), whereas Experience scores were higher in Video 2 ( W = 75,619, p < .001, r = 0.717). Reluctance to eat differed significantly ( W = 32,018, p < .001, r = 0.270), whereas guilt showed no significant difference ( W = 23,369, p = .103, r = 0.108). However, no significant relationship was observed between mind perception and either reluctance to eat or guilt. This study provides new insights into social interactions between humans and edible artificial objects, highlighting the potential of edible agents to deepen understanding of food culture and its ethical dimensions.